Influence of vanadium content and cooling rate on the characteristics of vanadium-alloyed spheroidal graphite cast irons - Kandemir, Acelya Sandikoglu; Gecu, Ridvan (ELSEVIER SCIENCE SA, 2023)
Spheroidal graphite cast irons (SGCIs) have been widely used in automotive and energy industries requiring excellent mechanical strength and wear resistance. This study aims to investigate the effects of vanadium content and cooling rate on the performance of these alloys. The SGCIs alloyed with different amounts of V (0, 0.25, 0.5, and 1 wt%) were fabricated at different section sizes (10, 20, 30, 40, and 50 mm) by the sand casting process for this purpose. The microstructural evaluation showed that V8C7 carbide density and pearlite ratio increased while ferrite volume decreased with increasing V content and decreasing section size. The number of graphite particles seemed to be inversely proportional to carbide precipitation. The more carbide caused the coarser graphite nodules with decreased nodularity. Thinner-wall castings provided a higher cooling rate resulting in better mechanical strength. Yield strength (YS), ultimate tensile strength (UTS), and hardness of SGCIs increased with increasing V and cooling rate. The minimum wear losses were achieved in 0.5 wt% V-alloyed SGCIs for all section sizes. Increased V8C7 carbide density in 1 wt% V-alloyed SGCIs significantly reduced impact toughness, causing decreased wear resistance despite their higher mechanical strength. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Spheroidal graphite; Cast iron; Vanadium; Microstructural evolution; Mechanical strength; MECHANICAL-PROPERTIES; DUCTILE IRON; MICROSTRUCTURE; CARBIDE; GROWTH; SIZE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering